Legal Status and Protection of Gig Economy Workers Under Indonesian Labor Law - Yosephine Fransisca Andriani; Atik Winanti; Aurora Jilena Meliala (Yayasan Cahaya Generasi Positif, 2026)
The rapid expansion of the digital gig economy exposes a severe normative vacuum within Indonesian labor law, permanently subjugating workers to exploitative algorithmic management and sham partnerships. Employing a doctrinal legal methodology, this study comprehensively evaluates Indonesia’s rigid statutory framework and conducts a comparative jurisprudential analysis with the United Kingdom and Spain. The findings indicate that dogmatic adherence to traditional employment classifications completely prevents algorithmic accountability, effectively externalizing operational risks onto entirely unprotected digital workers. Conversely, the UK’s hybrid 'worker' classification and Spain’s bold algorithmic transparency mandates provide vital blueprints. To prevent systemic disenfranchisement, Indonesia must immediately transition toward a responsive law paradigm by judicially piercing the digital corporate veil. The national legislature must formally codify a sui generis dependent contractor legal classification. Furthermore, institutionalizing an automated micro-levy social security mechanism alongside mandatory algorithmic transparency will perfectly balance essential labor protections with market flexibility, ultimately restoring substantive constitutional justice and fundamental human dignity.